Exploring perceptions on the influences of mentor-mentee relationships on graduate-student learning - Kuchinski, William (Kansas State University, 2023)
Academic mentoring relationships are frequently identified in the literature as important components of the learning experience; however, little research investigates how mentor-mentee relationships form and the effects of the relationships on learning. This study builds upon traditional mentoring theory, Cognitive Apprenticeship Theory, and other accepted academic mentoring frameworks to explore graduate students' perceptions of the influences of their mentor-mentee relationships on learning. In addition, the study includes a review of the literature on mentoring, mentoring in academic settings, and mentoring military students. This study used a qualitative, multi-case design to explore three mentor-mentee dyads at the beginning, middle, and end of the U.S. Army's Master of Military Arts (MMAS) graduate degree program. The mentors were all faculty members who served as MMAS committee chairs for their students. The study used reflective journals, semi-structured interviews, document reviews, field notes, and a conceptual framework based on Cognitive Apprenticeship Theory to explore student perceptions. Research guidance and feedback emerged as the primary themes aligned with how graduate students perceived they we challenged and supported by their mentors. Similarly, new perspectives, improved communication skills, and greater self-efficacy emerged as themes aligned with how graduate students perceived their relationships with their mentors influenced the acquisition or modification of existing knowledge, skills, and behaviors. The results of this study provide insights other researchers can use to understand better the importance of mentoring in academic settings, advance mentoring theory and its application in faculty development, and better prepare faculty and students to navigate their graduate-degree journeys.
Keywords: Mentor; Faculty; Development; Student; Graduate; Relationship